Mekah Kecil Di Tanah Besemah : Studi Terhadap Dinamika Perkembangan Islam di Desa Pardipe Kecamatan Dempo Selatan Kota Pagaralam - irpinsyah Irpinsyah; Nor Huda; Muhammad Syawaludin (Medina-te : Jurnal Studi Islam, 2019)
This research entitled "Small Mecca in the Land Besemah Study of the Dynamics of the Development of Islam in Pardipe Village" This study aims to explore the dynamics of the development of Islam in the village of Pardipe from the phase of the arrival of Islam to this day. This research includes field research with locations in Pardipe Village, South Dempo Sub-District, Pagaralam City, South Sumatra. This type of research uses a type of qualitative research, namely a procedure that produces qualitative descriptive data in the form of words, images, and not numbers, from people or observable behavior. While the source of data from this study is primary and secondary as for data collection in this study, the primary data source in this study is the source of data obtained through interviews and observations about the condition of the subject and object of research, secondary data sources in this study are various documents or archives, artepak, news, and books relating to problems in research. The results of this study can be concluded as follows the entry of Islam into the village of Pardipe was brought by a mubalihg named Syeh Nurqodim Al-Baharudin or better known as Puyang Awak. The dynamics that occur in the development of Islam in the village of Pardipe is like following a cycle, where there are phases appearing to develop and experience decline. There are several reasons why the village of Pardipe is referred to as the small Mecca, the first because the village was the first place for the entry of Islam on weak land. white people who often gather in the village